Clinical Usefulness of Klebsiella Pneumoniae Carbapenemase-Producing K. Pneumoniae Genotyping: The Experience of a Single-Center Epidemic - Marianna Rossi; Liliane Chatenoud; Egidio Franco Viganò; Anna Maria Peri; Laura Alagna; Simone Bramati; Monica Manenti; Monica Raggi; Annalisa Cavallero; Luca Bisi; Sebastiano Leone; Guglielmo Marco Migliorino; et al. (Case Western Reserve University, 2017)
Background: During the last decade, the spread of Klebsiella pneumoniae-carbapenemase-producing Klebsiella pneumoniae (KPC-Kp) has increased dramatically worldwide. In this scenario, growing interest has been addressed to genotyping of KPC-Kp strains, which emerged as an important tool for a better understanding of the epidemiological and clinical characteristics of the outbreaks. Methods: We performed a retrospective cohort study on patients infected with KPC-Kp during a 28-month outbreak period (January 2010-April 2012) at San Gerardo Hospital (Monza, Italy), investigating KPC-Kp genotypes by means of repetitive element sequence-based polymerase chain reaction (Rep-PCR). Results: We enrolled 97 patients infected with KPC-Kp. Rep-PCR analysis identified 5 distinct clone types, with different distribution over time. During the first 12 months of the outbreak period, only 1 clone was detected (clone A, in 47 patients), while the 4 other clones were identified over the remaining 16 months (clones C, E, and F/L in 23, 24, and 3 patients respectively). Mechanical ventilation was less frequent in patients infected with clones C/E/F/L (OR=0.14; 95% CI: 0.05-0.37) compared to clone A, and the Charlson comorbidity index (CI) was more likely to have a score >5 in patients infected with clones C/E/F/L (OR=7.21; 95% CI: 2.24-23.14) compared to clone A. Overall mortality was higher in patients infected with clones C/E/F/L (13/20 patients, 65%) compared to those infected with clone A (7/20, 35%). Mortality in patients infected with clones C/E/F/L remained significantly higher even after adjusting for the potential confounding effect of comorbidities (ie, CI), with a hazard ratio (HR) of 4.65 (95% CI: 1.83-11.89).